Continuous photochemistry - Penders, Inès Geerte Thea Maria (2017)
In this Thesis, several reactions are outlined, exploiting the diversity of photochemical substrates with both visible and UV light. The background of photochemistry and how it fits into the need for sustainable and selective synthesis routes is presented in Chapter 1. The Thesis is then divided into two parts, of which the first part focusses on the use of visible light for photochemical transformations. Chapter 2 describes the hydroxylation of aryl mono- and diboronic acids to their corresponding aryl alcohols employing white light LEDs. A 90-fold increase in productivity was achieved for the hydroxylation of phenylboronic acid to phenol by performing it in a continuous flow fashion as opposed to a more traditional batch fashion. Moreover, strategies for a more sustainable process were investigated such as (i) the use of a non-metal based photocatalyst (Rose Bengal), (ii) the use of supercritical carbon dioxide (scCO2) as the main solvent for phototransformations and (iii) the use of immobilised [Ru(bpy)3]Cl2 as the photocatalyst. A series of studies into reaction selectivity yielded moderate to high selectivities for the mono hydroxylation of para/meta/ortho-substituted aryl diboronic acids demonstrating the use of the reactors built in-house for desymmetrisation reactions. To show the scope of photochemical reactors, the use of a high pressure reactor indicated that highly efficient reactions can be obtained in this manner. The second part of the Thesis presents the use of UV light for photochemical transformations. Chapter 3 reports the formation of long-chain methyl ketones by the coupling of a ketone and an olefin. A recently developed excimer lamp based continuous flow photoreactor was utilised for this purpose and excimer lamps emitting at either 308, 282 or 222 nm were employed. Extensive investigation into the reaction parameters led to the selective formation of 2 undecanone via the coupling of 1-octene and acetone. Moreover, other sets of reaction conditions were identified to direct the product selectivity to several different reaction products. Chapter 4 describes the use of UV light for the dimerisation of ketones, primarily focussing on the dimerisation of acetone to acetonylacetone. This transformation is an example of an atom efficient and valuable reaction, but product yield was low. Several methods were explored to increase this yield, including (i) the use of a surfactant (sodium dodecyl sulfate) to create micellar solutions, (ii) the use of alternative photo absorbers such as sodium acetate or phthalimido acetate, and (iii) recirculating the reaction mixture. Preliminary studies were carried out on the dimerisation of several ketones other than acetone (2 butanone, acetophenone, pinacolone) as well. The work in this Thesis is summarised in Chapter 5 and suggestions for future work are presented. Chapter 6 describes details of the experimental procedures while Chapter 7 is the appendix containing the standard operating procedures for the equipment used in this Thesis.